Highlights in migraine electrophysiology: are controversies just reflecting disease heterogeneity?. Issue 3 (June 2016) - Magis, Delphine; Lisicki, Marco; Coppola, Gianluca
Abstract : Purpose of review: In migraine, the brain is 'hyperresponsive', which refers to a deficit of habituation to repeated sensory stimuli between attacks. This deficit normalizes in peri-ictal and ictal phases. A decreased cortical preactivation of thalamo-cortical origin and an impaired intracortical inhibition are probably involved in its pathophysiology. Recent findings: The reality of a habituation deficit of visual evoked potentials, a neurophysiological 'hallmark' of interictal migraine, has been questioned. Blinding may be an issue, but some genetic, environmental, or behavioural differences could also exist between populations. A habituation deficit is found interictally in other sensory modalities, and strongly depends on the time of the recordings within the migraine cycle. An impaired thalamocortical drive is demonstrated in interictal phase, and normalizes in ictal phase as well as in chronic migraine, where a strength enhancement of primary cortical activation is observed. An interictal dysexcitability, of subcortical or primary cortical origin, is suggested by magnetic stimulation. These phenomena could occur in varying degrees depending on patients and on the migraine cycle, and account for the heterogeneity of electrophysiological results. Summary: Finding a reliable electrophysiological biomarker for such a multifaceted and cycling disease as migraine is still a challenge. A better standardization of protocols would be worthwhile.